Pengaruh Fasilitas Belajar dan Motivasi Belajar Terhadap Hasil Belajar Materi Air Traffic Services Peserta Didik (Taruna) D.III Lalu Lintas Udara Angkatan IX Alpha & IX Bravo Pada Akademi Teknik dan Keselamatan Penerbangan Makassar - Irfan (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2018)
Achievement of student learning outcomes about factors, is a learning facility and learning motivation. The problem in this study is learning and learning facilities that are learned about student learning outcomes subject matter Air Traffic Service cadets D.III Air Traffic IX alpha & bravo at ATKP Makassar, the purpose of this study is that there is a Learning Facility and Learning Motivation on the learning outcomes of ATS material for students of D.III LLU class IX Alpha & IX Bravo Makassar ATKP to make all get a passing grade. The total migration population is 48 students. Researchers took the census technique, namely all participation as research objects. The research variables consist of independent variables namely learning facilities (X1) and learning motivation (X2) and motivation variables namely learning outcomes (Y). The data collection method uses questionnaires and settings. Data analysis uses descriptive percentage analysis. Conclusions are learning and learning facilities that are learned towards learning outcomes both simultaneously and partially. This research suggestion for good learning facilities to improve and improve learning facilities to maintain the existence of intensive vocational and care colleges must be regularly managed and monitored. on motivation to learn, motivation increases learners and teaching staff the purpose of donations issued and special competence in the field according to international standards.